Using REDItools to Detect RNA Editing Events in NGS Datasets. Issue 1 (15th February 2018) - Picardi, Ernesto; D'Erchia, Anna Maria; Montalvo, Antonio; Pesole, Graziano
Abstract: RNA editing is a post‐transcriptional/co‐transcriptional molecular phenomenon whereby a genetic message is modified from the corresponding DNA template by means of substitutions, insertions, and/or deletions. It occurs in a variety of organisms and different cellular locations through evolutionally and biochemically unrelated proteins. RNA editing has a plethora of biological effects including the modulation of alternative splicing and fine‐tuning of gene expression. RNA editing events by base substitutions can be detected on a genomic scale by NGS technologies through the REDItools package, an ad hoc suite of Python scripts to study RNA editing using RNA‐Seq and DNA‐Seq data or RNA‐Seq data alone. REDItools implement effective filters to minimize biases due to sequencing errors, mapping errors, and SNPs. The package is freely available at Google Code repository (http://code.google.com/p/reditools/ ) and released under the MIT license. In the present unit we show three basic protocols corresponding to three main REDItools scripts. © 2015 by John Wiley & Sons, Inc.